Aerodynamics of aero-engine installation - Stankowski, Tomasz P.; MacManus, David G.; Sheaf, Christopher T.; Grech, Nicholas (AIAA, 2016)
Small internal combustion engines, particularly those ranging in power from 1 kW to 10 kW, propel many remotely piloted aircraft (RPA) platforms that play an increasingly significant role in the Department of Defense. Efficiency of these engines is low compared to conventional scale engines and thermal losses are a significant contributor to total energy loss. Existing thermal energy loss models are based on data from much larger engines. Whether these loss models scale to the engine size class of interest, however, has yet to be established. The Small Engine Research Bench (SERB) was used to measure crank angle resolved gas temperature inside the combustion chamber of a small internal combustion engine (ICE). A 55 cc, two stroke, spark-ignition ICE was selected for this study. The engine was modified for optical analysis using sapphire rods 1.6 mm in diameter on opposite sides of the combustion chamber. The engine modification was found to have no measurable impact on indicated mean effective pressure or heat rejection through the cylinder. FTIR absorption thermometry was used to collect mid-infrared absorption spectra. The FTIR was allowed to scan continuously while simultaneously recording the scanning mirror position and crank angle associated with each data point, then data was re-sorted by crank angle. Measured spectra were compared with lines generated using CDSD-4000 and HITEMP line list databases. The line of best fit corresponded to the mean gas temperature through the combustion chamber. In this way temperature was determined as a function of crank angle for three operating conditions: 4,300, 6,000, and 7,500 revolutions per minute, all at wide open throttle. High cycle-to-cycle variation in the regions of combustion and gas exchange degraded temperature measurements at the affected crank angles. Future research will attempt to improve signal to noise in these measurements.